Peningkatan Kapasitas Petani Cokelat Desa Randualas Kecamatan Kare Kabupaten Madiun Melalui Edukasi Kualitas Kemasan Produk Cokelat - Achmad Ridwan Ariyantoro; Choirul Anam; Raden Baskara Katri Anandito; Danar Praseptiangga; Anastriyani Yulviatun (Universitas Sebelas Maret, 2021)
Increasing the Capacity of Chocolate Farmers in Randualas Village Kare District Madiun Regency through Education of Chocolate Product Packaging Quality. Cocoa is one of the largest commodities from Madiun Regency. Cocoa has the potential to be developed into processed chocolate products that will become typical souvenirs of Madiun Regency. The cocoa farmers in Randualas Village, Kare District, Madiun Regency have received counseling on the processing of cocoa beans into ready-to-consume chocolate products. However, the chocolate product was wraped in only an HDPE plastic layer which was less attractive to consumers, so it is necessary to improve the quality of the chocolate packaging. This community empowerment aims to increase the ability of cocoa farmers (partners) to package chocolate products properly and attractively so it will further increase the economic value of their chocolate product. The activities are education and counseling about the importance of packaging for chocolate products and how to design good and attractive packaging. Monitoring and evaluation were also carried out by filling out questionnaires by participants regarding the level of understanding of the material before and after being presented. The result showed that the partners understand the importance of packaging in food products in general and packaging for chocolate products in particular. It was evidenced that after counseling, up to 50% of participants understand the importance of packaging in the food packaging process and 50% of participants understand the criteria for good packaging for chocolate products.